Combining Mutations That Inhibit Two Distinct Steps of the ATP Hydrolysis Cycle Restores Wild-Type Function in the Lipopolysaccharide Transporter and Shows that ATP Binding Triggers Transport - Brent W. Simpson (American Society for Microbiology, 2019)
ABSTRACT ATP-binding cassette (ABC) transporters constitute a large family of proteins present in all domains of life. They are powered by dynamic ATPases that harness energy from binding and hydrolyzing ATP through a cycle that involves the closing and reopening of their two ATP-binding domains. The LptB2FGC exporter is an essential ABC transporter that assembles lipopolysaccharides (LPS) on the surface of Gram-negative bacteria to form a permeability barrier against many antibiotics. LptB2FGC extracts newly synthesized LPS molecules from the inner membrane and powers their transport across the periplasm and through the outer membrane. How LptB2FGC functions remains poorly understood. Here, we show that the C-terminal domain of the dimeric LptB ATPase is essential for LPS transport in Escherichia coli. Specific changes in the C-terminal domain of LptB cause LPS transport defects that can be repaired by intragenic suppressors altering the ATP-binding domains. Surprisingly, we found that each of two lethal changes in the ATP-binding and C-terminal domains of LptB, when present in combined form, suppressed the defects associated with the other to restore LPS transport to wild-type levels both in vivo and in vitro. We present biochemical evidence explaining the effect that each of these mutations has on LptB function and how the observed cosuppression results from the opposing lethal effects these changes have on the dimerization state of the LptB ATPase. We therefore propose that these sites modulate the closing and reopening of the LptB dimer, providing insight into how the LptB2FGC transporter cycles to export LPS to the cell surface and how to inhibit this essential envelope biogenesis process. IMPORTANCE Gram-negative bacteria are naturally resistant to many antibiotics because their surface is covered by the glycolipid LPS. Newly synthesized LPS is transported across the cell envelope by the multiprotein Lpt machinery, which includes LptB2FGC, an unusual ABC transporter that extracts LPS from the inner membrane. Like in other ABC transporters, the LptB2FGC transport cycle is driven by the cyclical conformational changes that a cytoplasmic, dimeric ATPase, LptB, undergoes when binding and hydrolyzing ATP. How these conformational changes are controlled in ABC transporters is poorly understood. Here, we identified two lethal changes in LptB that, when combined, remarkably restore wild-type transport function. Biochemical studies revealed that the two changes affect different steps in the transport cycle, having opposing, lethal effects on LptB’s dimerization cycle. Our work provides mechanistic details about the LptB2FGC extractor that could be used to develop Lpt inhibitors that would overcome the innate antibiotic resistance of Gram-negative bacteria.